The importance of the PLE (Personal Learning Environment) - Arroyo Sagasta, Amaia (Avances en Supervisión Educativa, 2013)
Learning should be a continuous process in our lives. This means that we must take into account the non-formal and informal learning, as they allow us developing the learning process throughout life. To achieve this, we have to find spaces that encourage learning and sources of knowledge.Internet is, above all, a communication space, but, in addition to communication opportunities it offers, we have to look at it from the perspective of learning. Communication urges to share information, to share the productions, in short, to share and create knowledge.Communication has made the leap to virtual world and gives us the opportunity to use resources, sources of information, make contacts... That shapes our PLE or Personal Learning Environment. Considering the great importance that has taken the Internet and new media, we can only emphasize its value and claim their place in formal education.